A Study of the Roles of a Local Network for Community Base Tourism in Khon Kae : Case Study Ban Nontan, Ban Thasongkhon and Ban Phratadn and Maha Sarakham Areas - Arjarasirikoon, Udchari; Khampuanbutra, Wanna; Najanthong, Mullika (Business Administration and Management Journal Review, 2020)
A study of the potential of a local network for community base tourism in Khon Khaen and Maha Sarakham areas. Methods and tools such as in-depth interview by using structured questionnaires with officials in government agencies responsible for tourist sites in 2 provinces. The population used in the research is staff in government agencies responsible for tourist attractions and personnel in the private sector, conducting in-depth interviews with structured interview questionnaires with 9 sample groups divided into Maha Sarakham Province, 6 people in Khon Kaen Province 3 people conducted in-depth interviews with officials in government agencies Personnel in the private sector and entrepreneurs Community leaders and villagers With a structured interview questionnaire with a sample of 40 people The results show that the local networks should be set for community base tourism at Ban Nontan Ban Thasongkhon and Ban Phratad. Each community has their function as follows, government section has duty as information advisor, non – government section has duty as service sector and community leader has duty as community networks and vocational production has duty as production sector for selling to tourists upon the capabilities of the communities. The strength of the areas is the temple as a center and cultural religion tourist attraction and a center of community. The weakness lack of development of tourist attraction places. Although these areas have main route to another, but their obstacle is government sector has limit budget to support the communities. According to the study, the 3 communities has shown the potential in cultural tourism management, the communities are readiness in culture and religious resources, government sector supporting development projects and tourism activities with collaboration form the villagers.